Melanotic neuroectodermal tumour of infancy: Case report of an unusual tumor - Agarwal P; Agarwal V; Raina V (Indian Journal of Plastic Surgery)
The melanotic neuroectodermal tumour of infancy is a rare, pigmented neoplasm of neural crest origin occurring in infants before 1 year of age. We report a 6-month-old male baby with a similar tumour involving superior maxillary alveolar ridge and most of the hard palate. A partial maxillectomy was performed by oral approach. One-year follow-up of the patient showed no recurrence.